Use of kefir peptide (Kef-1) as an emerging approach for the treatment of oxidative stress and inflammation in 2K1C mice. Issue 4 (28th January 2022) - Aires, Rafaela; Gobbi Amorim, Fernanda; Côco, Larissa Zambom; da Conceição, Amanda Pompermayer; Zanardo, Tadeu Ériton Caliman; Taufner, Gabriel Henrique; Nogueira, Breno Valentim; Vasquez, Elisardo Corral; Melo Costa Pereira, Thiago; Campagnaro, Bianca Prandi; dos Santos Meyrelles, Silvana
Abstract : In this study, an ACE inhibitor peptide synthesized from probiotic Kefir showed expressive biological activities in 2K1C hypertension. Abstract : The benefits of kefir consumption are partially due to the rich composition of bioactive molecules released from its fermentation. Angiotensin-converting enzyme (ACE) inhibitors are bioactive molecules with potential use in the treatment or prevention of hypertension, heart failure, and myocardial infarction. Here, the in vivo actions of the Kef-1 peptide, an ACE inhibitor derived from kefir, were evaluated in an angiotensin II-dependent hypertension model. The Kef-1 peptide showed a potential anti-hypertensive effect. Additionally, Kef-1 exhibited systemic antioxidant and anti-inflammatory activities. In smooth muscle cells (SMCs), the Kef-1 peptide decreased ROS production through the reduced participation of NADPH oxidase and mitochondria. The aorta of 2K1C mice treated with Kef-1 showed lesser wall-thickening and partial restoration of the endothelial structure. In conclusion, these novel findings highlight the in vivo biological potential of this peptide demonstrating that Kef-1 may be a relevant nutraceutical treatment for cardiovascular diseases.